EFFECTIVENESS OF LIFESTYLE INTERVENTIONS IN MANAGING CHRONIC MUSCULOSKELETAL PAIN - Kamil Rajczyk; Klaudia Jasik-Zawadka; Barbara Kujawa; Dominika Kozłowska; Paweł Jankowski; Antoni Dondajewski; Zuzanna Muszkiet; Wiktoria Musyt; Anna-Maria Grzeczka; Szymon Dudziński (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Chronic musculoskeletal pain, particularly low back pain (LBP), is a major global health issue, leading to reduced quality of life, disability, and a significant economic burden on healthcare systems. Increasing evidence suggests that lifestyle-related factors—including physical inactivity, poor sleep, obesity, and psychosocial stress—play a key role in the persistence and severity of chronic pain. Lifestyle medicine, emphasizing behavioral and non-pharmacological interventions, may offer promising therapeutic alternatives.Aim of the study: The aim of this review was to analyze the effectiveness of lifestyle-based interventions in the management of chronic musculoskeletal pain, focusing on non-pharmacological strategies and their clinical relevance in long-term pain modulation.Materials and methods: A systematic literature review was conducted using PubMed, Web of Science, and Google Scholar databases. The search included original studies published in English or Polish after 2013, focusing on adult populations and lifestyle-related interventions for chronic musculoskeletal pain. Studies were selected based on methodological quality and clinical relevance, following PRISMA guidelines.Results and conclusions: The analysis revealed that interventions such as cognitive functional therapy (CFT), occupational therapy, core stabilization exercises, aquatic therapy, abdominal drawing-in maneuver (ADIM), and telerehabilitation show positive effects on pain reduction, functional improvement, and patient engagement. Moreover, integrated healthy lifestyle behaviors—including physical activity, sleep hygiene, balanced diet, and weight management—were associated with reduced healthcare utilization and improved self-efficacy in pain management. Although current evidence supports the use of lifestyle interventions, further high-quality, long-term studies are needed to establish standardized clinical recommendations.